Developing a Framework of Media-Aided Descending-Ascending Repetition of Vocabulary Learning - Suwarsih Madya (Lingua Pedagogia, 2019)
Foreign language basic vocabulary learning for teenagers mostly belongs to verbal information learning, involving a lot of memorization and thus, necessary repetition. However, EFL teachers, particularly in the school observed, fail to pay attention to vocabulary learning at this stage due to limited time, which has resulted in low learning achievement.  This action research was focused on developing a framework of media-aided fading repetition of vocabulary learning for purposes of mastery improvement. The research participants were two English language teachers, one teacher educator, and 32 students in a state junior secondary school of a medium ranking and size in Sleman District, Yogyakarta Special Territory, Indonesia. This school was selected considering the transferability of the findings. The study was conducted from January-May 2017 in three planning-action-observation-reflection cycles of repeating the learning of the target vocabulary in the process of developing an appropriate framework of media-aided fading repetition in the existing curriculum implementation. Data were collected through observation and testing. The results were of two types: (1) the intended framework, and (2) improvement in the following aspects: the increasing classroom atmosphere liveliness, students’ greater participation, students’ increasing scores, and the teacher’s awareness of the importance of repetition and variations of activities in vocabulary learning. Keywords: vocabulary, EFL, media-aided descending-ascending repetition